Impact of obesity on outcomes after definitive dose‐escalated intensity‐modulated radiotherapy for localized prostate cancer. Issue 17 (29th May 2015) - Wang, Lora S.; Murphy, Colin T.; Ruth, Karen; Zaorsky, Nicholas G.; Smaldone, Marc C.; Sobczak, Mark L.; Kutikov, Alexander; Viterbo, Rosalia; Horwitz, Eric M.
Abstract : BACKGROUND: Previous publications have demonstrated conflicting results regarding body mass index (BMI) and prostate cancer (CaP) outcomes after definitive radiotherapy (RT) before the dose escalation era. The goal of the current study was to determine whether increasing BMI was associated with outcomes in men with localized CaP who were treated with dose‐escalated RT. METHODS: The authors identified patients with localized (T1b‐T4N0M0) CaP who were treated with definitive intensity‐modulated RT and image‐guided RT from 2001 through 2010. BMI was analyzed as a continuous variable. Adjusting for confounders, multivariable competing risk and Cox proportional hazards regression models were used to assess the association between BMI and the risk of biochemical failure (BF), distant metastases (DM), cause‐specific mortality (CSM), and overall mortality. RESULTS: Of the 1442 patients identified, approximately 20% had a BMI <25 kg/m 2, 48% had a BMI of 25 to 29.9 kg/m 2, 23% had a BMI of 30 to 34.9 kg/m 2, 6% had a BMI of 35 to 39.9 kg/m 2, and 4% had a BMI of ≥40 kg/m 2 . The median follow‐up was 47.6 months (range, 1‐145 months), with a median age of 68 years (range, 36‐89 years). The median dose was 78 grays (range, 76‐80 grays) and 30% of patients received androgen deprivation therapy. Increasing BMI was found to be inversely associated with age ( P <.001) and pretreatment prostate‐specific antigen level ( P = .018). On multivariable analysis, increasing BMI was associated with an increased risk of BF (hazard ratio [HR], 1.03; 95% confidence interval [95% CI], 1.00‐1.07 [ P = .042]), DM (HR, 1.07; 95% CI, 1.02‐1.11 [ P = .004]), CSM (HR, 1.15; 95% CI, 1.07‐1.23 [ P <.001]), and overall mortality (HR, 1.05; 95% CI, 1.02‐1.08 [ P = .004]). CONCLUSIONS: For patients with CaP receiving dose‐escalated intensity‐modulated RT with daily image‐guidance, increasing BMI appears to be associated with an increased risk of BF, DM, CSM, and overall mortality. Cancer 2015;121:3010–3017. © 2015 American Cancer Society . Abstract : Obesity is an epidemic affecting greater than one‐third of adults in the United States, and its incidence has more than doubled in the last 40 years. In the cohort of patients with prostate cancer in the current study, increasing body mass index appears to be associated with an increased risk of biochemical failure, distant metastases, and prostate cancer‐specific and overall mortality in patients treated with dose‐escalated intensity‐modulated radiotherapy and daily image guidance.